2013
DOI: 10.1038/onc.2012.575
|View full text |Cite
|
Sign up to set email alerts
|

MiR-152 and miR-185 co-contribute to ovarian cancer cells cisplatin sensitivity by targeting DNMT1 directly: a novel epigenetic therapy independent of decitabine

Abstract: Epithelial ovarian cancer (EOC) is a highly lethal gynaecological malignancy. Cisplatin is the basal chemotherapeutic agent used to treat EOC, but resistance to cisplatin leads to chemotherapy failure. MicroRNAs are a novel class of regulators that function by controlling gene expression at the post-transcriptional level. Several recent reports have identified some microRNAs that are related to chemotherapy sensitivity. In this study, we found two microRNAs miR-152 and miR-185 that were significantly downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
140
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 48 publications
6
140
3
Order By: Relevance
“…6,7 A second class modu-for drug transport or metabolism, including miR-24 (targets DHFR), 8 miR-451 and miR-27a (target MDR1), 9 miR-326 (targets ABCC1), 10 miR-328 and miR-519c (target ABCG2) 11 and miR-152 and miR-185 (target DNMT1). 12 All these findings suggest that miRNAs have emerged as a new platform for cancer therapeutics, and attempts to modify expression of selected miRNAs may lead to intriguing improvements in patient responses to chemotherapy.…”
mentioning
confidence: 99%
“…6,7 A second class modu-for drug transport or metabolism, including miR-24 (targets DHFR), 8 miR-451 and miR-27a (target MDR1), 9 miR-326 (targets ABCC1), 10 miR-328 and miR-519c (target ABCG2) 11 and miR-152 and miR-185 (target DNMT1). 12 All these findings suggest that miRNAs have emerged as a new platform for cancer therapeutics, and attempts to modify expression of selected miRNAs may lead to intriguing improvements in patient responses to chemotherapy.…”
mentioning
confidence: 99%
“…miR-185 was found to suppress glioma cell invasion, indicating that it may be a potential prognostic marker and therapeutic target (16). Previous studies have revealed that miR-185 impedes anchorage-independent growth, cell migration and invasion, in addition to suppressing tumor growth in vivo and increasing cisplatin sensitivity by promoting apoptosis, implicating it as a potent tumor suppressor (17)(18)(19). In the present study, overexpression of miR-185 repressed the growth and invasion of colon cancer cells in vitro and in vivo, which was consistent with the results of previous studies, indicating that miR-185 is a negative regulator of RhoA and Cdc42 and their cellular activities, and can inhibit the proliferation and invasion of CRC cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms contribute to cisplatin resistance such as a defective DNA repair system, enhanced drug clearance and detoxification, epigenetic regulation, and abnormal signaling pathways. 23,24 A growing body of evidence indicates a role of autophagy as a prosurvival and resistance mechanism against chemotherapy. With regards to cisplatin, recent studies demonstrated that cisplatin can induce autophagy in ovarian cancer cells through the ubiquitinbinding protein SQSTM1 or HMGB1 (high mobility group box 1).…”
Section: Discussionmentioning
confidence: 99%